Educational quality and new teaching-learning methodologies: challenges, needs and opportunities for a disruptive vision of the teaching profession (Innovaciones Educativas, 2021)
This study invites us to reflect on the needs and challenges that the current era leaves dormant, based on the realities and emerging situations that society faces today. Such is the case of the pandemic caused by the virus responsible for COVID-19, which has led to the necessary rethinking of educational systems and the forms of mediation and interaction that take place in the different learning ecosystems that have been transformed. Based on the current scenario, questions arise such as, how to sustain educational quality considering the changes that occur in an accelerated way. On the other hand, how to create awareness in teaching professionals about a necessary rethinking of the teaching profession, which allows them to transform those scenarios of uncertainty and challenges they face into opportunities to improve their work. Regarding what has been said, this essay will carry out an analysis on several issues related to educational quality and the search for new teaching-learning methodologies (TL) for comprehensive training. As well as the implications of the educational actors involved with the quality of education in order to meet the emerging socio-educational needs. Also, the rethinking of the teaching profession from a disruptive vision, which suggests transforming the challenges and demands experienced into opportunities, making it possible to go from being a trainer to a self-managing agent of improvements and promoter of active methodologies that guarantee thecomprehensive and competent education of citizens.
Keywords: quality of education; inclusive education; active learning; skills development; ecosystem; student-teacher; information technology